Toward optimizing new nurse anaesthetist training: a qualitative study of perceptions, experiences, and systemic challenges - Tingting Yang; Xueyan Xing; Ying Sun; Jiale Hu; Jiamin Kang; Shumin Tu (BMC Nursing)
Abstract Background In China, most new nurse anaesthetists graduate from general nursing programs and initially lack anaesthesia-related knowledge, skills, and abilities. Additionally, the absence of uniform training standards for new nurse anaesthetists in China means that many are unable to provide comprehensive anaesthesia care. Objectives This study was conducted to understand the perceptions, experiences and systemic challenges for conducting training for new nurse anaesthetists in anaesthesia from the perspectives of both junior nurse anaesthetists who had received a full induction and the training implementers: (1) understanding the experiences and needs of the training process from the perspective of a junior nurse anaesthetist who has received a full induction programme. (2) understanding the recommendations of training implementers (anaesthesiologists educators, administrators, and anaesthesia nursing educators, administrators) on training implementation. Methods Semi-structured interviews were performed with a purposive sample of 14 participants, comprising junior nurse anaesthetists, anaesthesiologists educators, administrators, and anaesthesia nursing educators, administrators. The data were analyzed using Colaizzi’s seven-step method to distill the participants’ real feelings, suggestions, and training needs, which were then grouped into sub-themes and themes to provide a structured understanding of the training dynamics. Results Four primary themes and ten sub-themes were identified through the analysis. The themes include: (1) characteristics of new nurse anaesthetists; (2) clarification of the role of new nurse anaesthetists and establishment of training content in accordance with job requirements; (3) formation of a diversified teaching method and design of an evaluation system based on the teaching content; and (4) increased attention to new nurse anaesthetists as individuals and to their future development. These themes and sub-themes provide a detailed and structured overview of participants’ perceptions, experiences, and systemic challenges from the training. Conclusions This study demonstrates that the training has positively influenced the new nurses’ perception of anaesthesia nursing and their job competence. Despite these improvements, several critical steps are necessary to enhance the training’s effectiveness and quality. These include carefully selecting and screening trainers, optimizing the training content, addressing stress during the training period, and integrating future career planning into the training program. These measures will contribute to a more comprehensive and supportive training experiences for new nurse anaesthetists. Clinical trial number XZHMU-2024Y001(20240103).